The Redeemed Christian Church of God (rccg), Nigeria. Local Identities and Global Processes in African Pentecostalism - Ukah, Asonzeh (2003)
This study documents the history and growth of the Redeemed Christian Church of God (RCCG). The RCCG is a pentecostal church in Nigeria, established in 1952, but was little known until the 1990s when it came into national prominence. It was founded by Josiah Akindayomi who was converted form Yoruba religion into the Church Missionary Society (CMS). He left the CMS to join the Cherubim and Seraphim (C&S), one of the emerging African Independent Churches (AICs). From here, he founded his own independent church which in subsequent years developed into a pentecostal church. The RCCG is one of many pentecostal churches existing in Nigeria. Although some research exists on Nigerian Pentecostalism, there is almost nothing on the RCCG. The present study presents a case study which deals with Pentecostalism in Nigeria and tries to relate it to globalisation discourse. It is the first such study from Africa. Its contribution is in providing a case study on a religious group that also relates to contemporary processes which, some scholars have argued, have side-stepped Africa (Brouwer et al. 1996; Gifford 1998; 2001; Cooper 2001). It builds on, and follows the scholarly tradition of Peel (1968; 2000); Hackett (1987; 1989); Marshall-Fratani (1998). These scholars have worked on the Nigerian religious sphere by combining History of Religions and social scientific approaches. The study is made up of three parts. Part one is composed of the historical section comprising chapters 2 and 3 which includes the biographies of the founder of RCCG and his successor. Part two is the descriptive section which is made up of chapters 4, 5 and 6. This section focuses on organisational structure, institutions, doctrines and rituals of the RCCG. Chapter 4 presents the organisational structure of the church at the present period. It also discusses some of the para-church groups, schools, media use, finance and the place of women in the church. Chapter 5 examines the belief system while chapter 6 presents the ritual activities of the church. Part 3, which consists of chapter 7, is the theoretical reflection on our case study. While the RCCG has grown by reinterpreting its doctrines in line with local social, economic, political and cultural situation, part of its appeal to a broad spectrum of people, groups and organisations is its marketing strategies as well as its relationship with global economic players such as Coca-Cola company, Procter and Gamble, a wide range of manufacturing companies, banks and other financial institutions which provide scarce human and economic resources for the churchs social, religious, economic and political mobilisation in Nigeria. Die Studie dokumentiert die Entstehung und Entwicklung der Redeemed Christian Church of God (RCCG). Die RCCG ist eine pentekostale Kirche in Nigeria. Sie wurde 1952 gegründet, war aber recht unbekannt, bis sie in den 1990er Jahren nationale Berühmtheit erlangte. Sie wurde von Josiah Akindayomi gegründet, der von der Religion der Yoruba zur Church Missionary Society (CMS) konvertierte. Er verließ die CMS, um sich der Cherubim and Seraphim (C&S) Bewegung, einer der afrikanischen unabhängigen Kirchen (African Independent Churches, AIC), anzuschließen. Vor diesem Hintergrund gründete er seine eigene unabhängige Kirche, die sich in den nachfolgenden Jahren zu einer pentekostalen Kirche entwickelte. Die RCCG ist eine von vielen in Nigeria existierenden pentekostalen Kirchen. Es wurde zwar schon viel zum nigerianischen Pfingstkirchentum geforscht, zur RCCG liegt jedoch fast nichts vor. Die vorliegende Arbeit stellt eine Fallstudie vor, die mit dem Pfingstkirchentum in Nigeria befasst ist und versucht, dieses mit dem Globalisierungsdiskurs in Beziehung zu setzen. Es ist die erste Studie dieser Art über ein Beispiel aus Afrika. Ihr Beitrag liegt darin, eine Fallstudie über eine religiöse Gruppe zu präsentieren, die an gegenwärtige Prozesse anknüpft, von denen manche Wissenschaftler behauptet haben, dass sie Afrika umgangen hätten (Brouwer et al. 1996; Gifford 1998; 2001; Cooper 2001). Sie baut auf der wissenschaftlichen Tradition von Peel (1968; 2000), Hackett (1987; 1989) und Marshall-Fratani (1998) auf und setzt diese fort. Diese Forscher verwenden in ihren Arbeiten zu den nigerianischen Religionen eine Kombination von religionshistorischen und sozialwissenschaftlichen Ansätzen. Die Arbeit besteht aus drei Teilen. Der erste Teil bietet eine allgemeine Einleitung, in der der historische Kontext, die Forschungsgeschichte, die Fragestellung und der methodische Ansatz dargestellt werden. Der zweite, umfangreichste Teil bietet zunächst einen historischen Abschnitt (Kapitel 2 und 3), der die Biographien des Gründers der RCCG und seines Nachfolgers enthält. Der zweite Abschnitt (Kapitel 4-6) ist deskriptiv und konzentriert sich auf die Organisationsstruktur, Einrichtungen, Lehrsätze und Rituale der RCCG. In Kapitel 4 wird die Organisationsstruktur der Kirche zum gegenwärtigen Zeitpunkt vorgestellt. Einige der para-kirchlichen Gruppen, die Schulen, die Verwendung von Medien, die Finanzen und die Stellung von Frauen in der Kirche werden ebenfalls diskutiert. In Kapitel 5 wird das Glaubenssystem untersucht, während in Kapitel 6 die rituellen Aktivitäten der Kirche dargestellt werden. Der dritte Teil, der aus Kapitel 7 besteht, enthält die theoretische Reflexion über unsere Fallstudie.
Free